PEMAHAMAN PANDUAN OPERASIONAL PENYELENGGARAAN BIMBINGAN DAN KONSELING TINGKAT SMP - Ali Rachman; Akhmad Sugianto; Sri Yustina (JURNAL BIMBINGAN DAN KONSELING AR-RAHMAN, 2020)
Undang-undang Republik Indonesia Nomor 14 Tahun 2005 tentang Guru dan Dosen dan Peraturan Pemerintah Republik Indonesia Nomor 37 Tahun 2009 tentang Dosen bahwa Kompetensi Guru dan Dosen terdiri dari kompetensi pedagogik, profesional, sosial dan kepribadian. Berdasarkan hal tersebut guru bimbingan dan konseling harus mampu dalam menyelenggarakan layanan bimnbingan dan konseling. Penyelengaraan bimbingan dan konseling di sekolah sudah berpedemoan kepada panduan operasional penyelengaaran bimbingan dan konseling. Urgensi penelitian adalah untuk mengetahui pemahaman guru bimbingan dan konseling terhadap panduan operasional penyelenggaraan bimbingan dan konseling di tingkat SMP serta untuk mengetahui hasil penerapan panduan operasional penyelenggaraan bimbingan dan konseling di tingkat SMP. Secara metodologis, penelitian ini didasarkan pada penelitian kuantitatif  dengan jenis penelitian survei. Tujuan penelitian yaitu menggambarkan tingkat pemehaman guru bimbingan dan konseling terhadap panduan operasional penyelenggaraan bimbingan dan konseling di tingkat SMP Se-Kabupaten Tabalong. Adapun jumlah responden dalam penelitian ini adalah 37 orang dari 35 sekolah Menegah tingkat Pertama di Kabupaten Tabalong.__________________________________________________________Republic Indonesia Law Number 14 of 2005 concerning Teachers and Lecturers and Republic of Indonesia Government Regulation Number 37 of 2009 concerning Lecturers namely Teacher and Lecturer Competencies consists of several competencies namely Professional, Social, Personality & Pedagogic. Based on this the BK teacher must be able to implement the BK program. The organization of BK has demonstrated to the operational guidelines for conducting guidance and counseling. The urgency of the research is to see how far Bk teachers understand POP BK at the SMP level on aspects of the SMP POPBK concept, basic services, specialization and individual planning, responsive services and system support. Methodologically, this research is based on quantitative research. The purpose of the study is to describe the level of understanding of BK teachers against BK BK at the Junior High School level in Tabalong Regency. The number of samples in this study were 37 people from 35 Menegah First level schools in Tabalong Regency. The technique used in sampling is purposive sampling. Based on the results of research conducted, it was found that the understanding of guidance and counseling teachers on the concept of POP BK SMP 89% in the category of very understanding. Basic services 81% of the categories are very understanding, specialization services and individual planning 91% in the category of very understanding, responsive services 59% are quite understanding and support systems are 79% in the categories of understanding.